Design of Drainage System Coal Mine at PT. Tebo Agung International Site Project, Semambu Village, Sumay District, Tebo Regency, Jambi - Muhammad Reynaldi (Journal of Earth and Marine Technology (JEMT), 2021)
Tebo Agung Internasional Ltd is one of the companies in coal mining that employs the open-pit mining method. This sort of method will create a large basin that can accumulate water inside the mining pit. The drainage system is applied at the Pit-1 Site Semambu is mine-dewatering carried out by draining the water into the sump so that it can be pumped out of the mining area and prevent the runoff from coming inside through an open drainage system (ditch). The result of data analysis demonstrated that referring to the daily rainfall in 2010 – 2019 through the distribution of Log Person Type III, the maximum rainfall being planned was 508.019 mm/day within the return period of 5 years. The intensity of rainfall at the research site was 82.5 mm/hour having a rain duration averagely of 3.1 hours/day. Pit-1 Site Semambu had a catchment area around 469,317.15 m2 and a water discharge totally 61,238.81 m3/day derived from rainwater discharge of 48,530.48 m3/day and runoff water discharge 12,708.33 m3/day, whereas the capacity of the temporary accommodating pond (Sump) was 39,539.55 m3. The pump at the research site could not be operated anymore (broken). Accordingly, the recommendation that can be given to the company is changing the broken pumps with 4 units of multi fall 420 pumps having operating speed 1,300 rpm and actual discharge yielded by the pump 871.64 m3/hour. The pump worked for 14 hours/day and the total water discharge that could be produced was 12,202.96 m3/day. Open channel (ditch) at Pit-1 Site Semambu was the only one with accommodated discharge 1.27 m3/second. Thus, the recommendation that could be delivered to optimally prevent the runoff water coming into the mining area is by adding 2 ditches having the capacities of 0.90 m3/second and 0.75 m3/second which have been adjusted to the planned water discharge.